A dynamic bandwidth schemes base on adaptive video streaming - Issa, Sinzobakwira; Khalifa, Othman Omran; Gunawan, Teddy Surya (Center Transylvanian Studies, 2017)
Nowadays, with the current state-of-art technology, users’ streaming where individual users normally named peers cooperatively distribute videos, is one of todays’ applications which is very crucial. The major challenge to Internet Service Providers is, as size of users goes up, the bandwidth needed increases as well, complicating the distribution of the bandwidths to be consumed. Video distributions as well as viewers have their demands. Servers, channel capacity and video qualities demand by users are also other constraints. As such it is very important to design an efficient system to cope with uneven demands of bandwidth for areas with high demographic density. The aim of this paper is to design an adaptive video streaming based on neighboring resource sharing. An adaptive system based on bandwidth sharing approach is proposed. In this experiment, Joint Scalable Video Motion (JSVM) software was used with 100 as a number of users. The arrival of users is considered to be exponential. The experimental result shows that the algorithm proposed achieve better video quality when the number of neighboring helpers increases by reducing playback delays. However this also increases the computational complexity. The experiment shows promising solution to both academia and ISPs in order to plan for future challenges in order to meet users’ demands in terms of bandwidth.